“When David Bowie created Ziggy Stardust” Reconceptualising workplace learning for social workers - Ferguson, Gillian (The Journal of Practice Teaching and Learning, 2023)
This article draws on phenomenological research offering new insights into workplace learning for social workers. The qualitative study explored social workers’ experiences of learning in the workplace. The structure, texture and meaning of these lived experiences were described using sensory details and striking metaphors. Drawing on the study findings, a web model for reconceptualising workplace learning for social workers is introduced. This web is woven from connected themes: journey of the self; navigating landscape and place; navigating tasks; learning through others; learning through the body; practices and conceptions of learning; and learning by chance. The discussion will show the complexity of social workers’ experiences and how understanding these can foster effective workplace professional learning. Workplace learning needs valued beyond rhetoric in professional development strategies. The research restores the importance of direct practice as a primary career-long and career-wide professional learning solution.